Application of N-Acetyl-Glucosaminil-N-Acetyl-Muramyl Dipeptide during Triple Component Anti-Helicobacter Pylori Therapy in the Period of Coronavirus Infection COVID-19 - M. R. Konorev; E. N. Tyshevich; R. A. Pavlyukov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: evaluation of the incidence of COVID-19 infection after three-component H. pylori eradication therapy while taking N-acetyl-glucosaminyl-N-acetyl-muramyl dipeptide (GMDP).Materials and methods. A prospective randomized comparative clinical study was carried out. The study included 208 patients (147 men, 61 women; mean age — 48.1 ± 14.5 years) with duodenal ulcer associated with Helicobacter pylori (H. pylori) who underwent eradication therapy. H. pylori in the gastric mucosa was detected by a morphological method and a rapid urease test before treatment and 6-8 weeks after the end of treatment and the withdrawal of all drugs. Patients were divided into three groups according to treatment protocols: omeprazole 0.04 g/day, clarithromycin 1 g/day, amoxicillin 2 g/day (OСA; n = 103); omeprazole 0.04 g/day, clarithromycin 1 g/day, amoxicillin 2 g/day + GMDP 0.001 g/day (OCAL1; n = 61) or 0.01 g/day (OCAL10; n = 44) for 10 days. Detection of SARS-CoV-2 RNA by PCR was carried out from April 2020 to April 2022. Tracking completeness was 96.6 %.Results. The frequency of H. pylori eradication depending on “intention to treat” (ITT) and “per protocol” (PP): OCA — 79 % (95 % CI: 71-87) and 83 % (95 % CI: 75-91); OCAL1 — 95 % (95 % CI: 88-100) and 97 % (95 % CI: 92-100); OCAL10 — 96 % (95 % CI: 89-100) and 98 % (95 % CI: 93-100) respectively. The frequency of adverse reactions depending on ITT and PP: OCA — 24 % (95 % CI: 16-33) and 26 % (95 % CI: 17-35); OCAL1 — 2 % (95 % CI: 0.01-8) and 2 % (95 % CI: 0.01-8); OCAL10 — 2 % (95 % CI: 0.01-7) and 2 % (95 % CI: 0.01-7). The incidence of COVID-19 infection depending on ITT and PP: OCA — 9 % (95 % CI: 3-14) and 9 % (95 % CI: 3-15); OCAL1 + OCAL10 — 1 % (95 % CI: 0.003-1.9) and 1 % (95 % CI: 0.001-2.9), respectively.Conclusions. In H. pylori-infected patients, GMDP (an immunomodulator based on L. bulgaricus) at a dose of 1-10 mg/day, during a 10-day triple eradication therapy, allows a significant (p < 0.05) increase in the frequency of H. pylori eradication and reduce the incidence of adverse reactions compared with a 10-day protocol without adjuvant therapy with GMDP. There was a significant (p < 0.05) decrease in the incidence of COVID-19 infection after H. pylori eradication therapy with GMDP.